Empowerment, Self-Efficacy, and Teacher Performance: The Mediating Role of Employee Engagement in Foundation-Based Private Schools in West Kalimantan, Indonesia - Yopita, Yopita; Ginting, Sunardi (Jurnal Economic Resource, 2026)
Teacher performance is a cornerstone of educational quality, yet the mechanisms driving it in foundation-based private schools remain insufficiently understood. This study examined the effects of empowerment and self-efficacy on teacher performance, mediated by employee engagement, among 94 teachers in schools under Yayasan Amkur, West Kalimantan, Indonesia. Grounded in the Job Demands-Resources model and Bandura's Social Cognitive Theory, seven hypotheses were tested using PLS-SEM via WarpPLS 7.0. All hypotheses were supported. Empowerment and self-efficacy positively predicted employee engagement, with empowerment as the stronger predictor. Both independently influenced teacher performance, with self-efficacy exerting a stronger direct effect. Employee engagement was the dominant predictor of teacher performance and partially mediated both upstream relationships. The model explained 88.3% and 87.4% of variance in engagement and performance respectively. These findings extend the JD-R framework to Indonesian foundation-based schools and highlight employee engagement as the central mechanism converting organizational and personal resources into superior teacher performance.